2023
DOI: 10.3233/jad-230551
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Phosphorylated Tau in Alzheimer’s Disease Induced Pluripotent Stem Cell-Derived Neuro-Spheroids by Rho-Associated Coiled-Coil Kinase Inhibitor Fasudil

Elisa Giunti,
Roberto Collu,
Sarah Daley
et al.

Abstract: Background: Alzheimer’s disease (AD) is the most predominant form of dementia. Rho-associated coiled coil kinase (ROCK) inhibitor, fasudil, is one of the candidate drugs against the AD progression. Objective: We aimed to investigate possible changes of AD associated markers in three-dimensional neuro-spheroids (3D neuro-spheroids) generated from induced pluripotent stem cells derived from AD patients or healthy control subjects (HC) and to determine the impact of pharmacological intervention with the ROCK inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…We recently found that fasudil was able to reduce the increase of pTau at different residues (i.e., pTau-202, −231, and −396) in Alzheimer's induced pluripotent stem cell-derived neurospheroids via clusterin (clu) and the AKT serine/threonine-protein kinase 1 (AKT1) (Giunti et al, 2023 ). In our PS19 mice, treatment with fasudil significantly affected tau phosphorylation in the brain in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that fasudil was able to reduce the increase of pTau at different residues (i.e., pTau-202, −231, and −396) in Alzheimer's induced pluripotent stem cell-derived neurospheroids via clusterin (clu) and the AKT serine/threonine-protein kinase 1 (AKT1) (Giunti et al, 2023 ). In our PS19 mice, treatment with fasudil significantly affected tau phosphorylation in the brain in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%